A novel approach to integrating the stability of river ecosystem and its driving factors - Yue, Ziqi; Fang, Qingqing; Zhang, Shanghong; Wu, Chuansen; Wang, Le (Frontiers in Environmental Science, 2025)
IntroductionIn recent years, river ecosystem stability has been increasingly threatened by human activities and climate change. Comprehensive quantification of river ecosystem stability and systematic analysis of its response to human activities and climate change are essential for effective conservation and management.MethodsThus, this study proposed a novel quantitative approach to integrating the stability of river ecosystem and its driving factors. The Han River Basin in China was selected as the study area due to its distinctive climate characteristics and significant anthropogenic impact. Both external factors, including urbanization, dam construction, and precipitation, and internal factors, such as TP, DO, and EC, were considered as driving factors.ResultsThe results revealed that compared to the upstream, resilience in the lower reaches decreased by 35.75% and the resistance decreased by 8.2%, suggesting that the stability decreased from upstream to downstream. Urbanization had the most significant negative impact on ecosystem stability, followed by precipitation and dam construction. Among the internal factors, TP, DO, and EC were the three main factors affecting ecosystem stability and the increases in these factors contributed positively to enhancing ecosystem stability.DiscussionThese findings highlight the need for targeted conservation strategies to mitigate human-induced disturbances and enhance river ecosystem stability. Based on the results, specific recommendations were proposed to support watershed management and ecological restoration, providing valuable insights for sustainable river conservation.